Replacement name for the homonym of subgenus Trimorus (Neotrimorus) (Hymenoptera: Platygastroidea: Scelionidae) with description of two new species from India. Issue 41 (17th November 2022) - Veenakumari, Kamalanathan; Keloth, Rajmohana; Sreedevi, Kolla; Kumar, P. Girish; Mohanraj, Prashanth
ABSTRACT: Trimorus ( Lochana ) nom. nov. is proposed as a replacement name for the subgenus Trimorus ( Neotrimorus ) (Hymenoptera: Scelionidae), a junior homonym of Neotrimorus Dalla Torre (Hymenoptera: Braconidae). This subgenus has a distinct striated medial mesoscutellar spine as well as basal depressions on the third metasomal sternum. 'Basal depressions on the third metasomal sternum', earlier considered to be present only in Xenomerus in Teleasinae, are now found to be shared by Trimorus ( Lochana ). Two new species, Trimorus ( Lochana ) karna sp. nov. and T . ( L .) satyaki sp. nov., are described and illustrated. The following new combinations are proposed: Trimorus ( Lochana ) spinostriatus comb. nov.; T . ( L .) scutellospinosus comb. nov.; T . ( L .) ferrari comb. nov. Keys to the females and males of all species of Trimorus ( Lochana ) are provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:C054A157-803A-4E9F-B2A1-ABEB88EAD4F1